Postponement and the wealth of nations - Andreas Rutsch; Christian-Andreas Schumann; Jörg W. Wolle (OrdnungsPolitisches Portal (OPO), 2010)
In this paper, Fair Value Chain Creation (FVC2;), as an approach that applies and extends principles of Fair Trade to exports from developed countries to the less developed countries, is being introduced. It awards a Fair Value label to goods which undergo further value adding in the host market. FVC2; attempts to utilize a label pointing at made for rather than made in by emblematizing the degree of Fair Value involved. Building on logistics and manufacturing postponement allows FVC2; to balance value chains in such a way that both stakes (North - South; developed countries - developing countries; country of origin - host market) are going to profit. Developing countries can increase their share in value chains originating from Northern countries. In turn, this enables those developed countries and corresponding manufacturers to level their resources. While postponing none-core activities to the developing countries and the respective host markets, manufacturers can focus even more on core processes. In fact, FVC2; mostly employs humans instead of machines. It makes labor a promoted option. Based on free-market mechanisms, like opportunity costs and the production possibilities frontier, the authors prove FVC2; being an attempt in the market and on the structure of global value chains. Fair Value Chain Creation is driven by enhanced global logistics performance. Thus, and in contrast to Fair Trade, FVC2; requires no price premium being paid by the consumer and therefore no stringent inspection of its application. Nonetheless, every labeling initiative requires an authority to prevent malpractice. The authors show, before such an initiative can be put into practice, that it is particularly evident to define the developing gap enabling to specify the potential and spectrum of FVC2;. This gap arises from globalization and enhanced logistics performance (foremost postponement).
Keywords: 330; Fair Trade; Fair Value Chain; Fair Value Creation; Postponement; Wealth of Nations; Fairer Handel; Herkunftsbezeichnung; Betriebliche Wertschöpfung; Logistik; Nord-Süd-Beziehungen; Welt